Bridges and hobby-horses: John Stewart's adventure of ideas. (October 2021) - Di Paolo, Ezequiel A
I briefly reflect on the work of John Stewart and his instrumental role in the development of enactive cognitive science, his outstanding ability to communicate across disciplines, and his research obsessions.